ANALYSIS OF IMPROVEMENT CAUSING DAMAGE TO CYLINDER LINERS AND PISTON RODS IN VEHICLE MODELS (F65 # -3SZ) - Cecep Deni Mulyadi (ENSAINS JOURNAL, 2019)
Abstract: Cases that occur complaining about the engine on the vehicle is abnormal, both in idling and high rpm, when the initial inspection is carried out, there appear to be abnormal symptoms on the vehicle's engine.So it needs repairs to the vehicle where there is a problem in the vehicle, which complains about the abnormal state of the engine both the state of idling or middle and high rpm.After doing repairs, the problems that occur occur. The water hammer is caused by a cowl top seal that has no locking clip and water filter assembly. As a result of the water hammer being produced, there is damage to the components inside the cylinder block, namely the cylinder liner and piston rod.Keywords: Abnormal, When Idling, High Rpm